Blistering in Cu2ZnSnS4 thin films: correlation with residual stresses. (15th October 2016) - Malerba, C.; Valentini, M.; Azanza Ricardo, C.L.; Rinaldi, A.; Cappelletto, E.; Scardi, P.; Mittiga, A.
Abstract: An investigation is presented on the blistering of Cu2 ZnSnS4 (CZTS) thin films grown by sulfurization of co-sputtered quaternary precursors. SEM cross-sectional images of post-annealed samples show film delamination occurring at the CZTS/substrate interface, with formation of blisters whose diameter typically ranges between 10 and 60 μm and height between 3 and 10 μm. Two main competing mechanisms suggested by the literature on different materials have been considered to explain blistering in CZTS, respectively based on the relief of compressive stress or on the formation of over-pressurized trapped-gas bubbles. Intrinsic residual stress in as-sputtered precursor layers was measured by substrate-curvature and by X-ray diffraction techniques. Results show that by increasing the sputtering pressure both compressive stress in precursors and blistering extent in the corresponding CZTS film decrease. A mechanism based on stress-driven viscoplastic deformation is proposed to explain blistering in CZTS films, while trapped-Ar pressure seems to play just a secondary role. Graphical abstract: Highlights: Blistering effect in Cu2 ZnSnS4 thin films grown by sulfurization of co-sputtered quaternary precursors is investigated. Intrinsic in-plane residual stresses in as-sputtered films are studied using both substrate-curvature and XRD techniques A correlation between the compressive stress in precursors and the blistering extent in the annealed films is shown. Intrinsic stresses in precursors and blistering extent can be reduced and suppressed by increasing the sputtering pressure. A stress-driven model in viscoplastic conditions is proposed as the main mechanism to explain blistering in Cu2 ZnSnS4